Riscos e escritos no confinamento: uma análise do processo de troca de cartas com adolescentes em medida socioeducativa durante a pandemia da Covid-19 - Weber, André Morgental (2022)
This master's dissertation work presents an analysis of the exchange of letters activity established between university extension workers and adolescents deprived of liberty during the Covid-19 pandemic. The exchanges of letters were established in the context of an extension project that carried out psychosocial intervention groups with adolescents who were serving socio-educational measures at the Centro de Atendimento Socioeducativo Regional de Santa Maria (CASE-SM), located in the central region of Rio Grande do Sul. During the development of face-to-face activities, several issues such as the body, the position of the subject, the speeches, among others, made it possible for writing activities, drawings, tattoos, among others, to be developed in order to make it possible to give voice and enable accountability. the same for teenagers. In-person activities took place until 2020, when they were interrupted due to the Covid-19 pandemic. With this, the exchange of letters began, initially designed to promote the maintenance of a bond between extension workers and adolescents, but, in the course of the exchanges, an important potential for an intervention was constituted, as the adolescents signed up / wrote in the letters sent to the group and to each member. From this, the proposal of analysis of this process was formulated, relating it to the psychoanalytic theory and approaching in a more specific way the dimensions of writing, aggressiveness and the body. The results of this analysis are structured in three chapters: The first chapter refers to the history of the workshops, presenting the beginning of activities with adolescents, in 2016, the main activities developed in the following years in person (2017-2019), culminating in the beginning of the activity of sending letters in the year 2020. The second chapter focuses on the work of exchanging letters with adolescents in the perspective of analyzing the writing process and a possible corporeality derived from this process. The third chapter uses the same activity of exchanging letters to think about the relationship between aggression and writing. Taken together, the results of the dissertation indicated that it is possible to use different devices to enable adolescents to express themselves, either through speech or writing, operating important discursive slides for the process of subjective constitution, especially in a context of deprivation of liberty.